The economic history of Silesia in the Polish-German academic dialogue after 1945 (overview) - Belzyt, Leszek C. (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The impressive development of industry in Silesia was reflected in many works of Polish and German historians after 1945. Differences in assessments are generally small, and those that do exist are mainly due to different national positions. These differences relate in particular to the crisis situation after 1918 and the division of Upper Silesia. After 1989, evaluations of this kind occur incidentally, and rather just in publications of a popular-science character.
Keywords: history of historiography; Silesia; industrialisation; German-Polish relations